EDUCATION AND SOCIALIZATION OF PSAK 72 AND ITS AUDIT PROCEDURE IMPLICATIONS THROUGH FREE NATIONAL WEBINAR - Magdalena, Renna; Sihombing, Tanggor; Karyawati, Golrida; Risty, Illyona; Herbert, Go George; Tjahjono, Josephine Kurniawati (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
Auditing is essential in ensuring the appropriateness of financial reports, the accuracy of company operations, and compliance with applicable regulations. One of the regulations governing audit procedures is PSAK 72, which establishes the essential steps in recognizing revenue from contracts with customers. Even though it has been published since 2017, implementation of PSAK 72 is mandatory starting in 2020. To help understand the implications and application of PSAK 72, a webinar entitled "PSAK 72 and the Implications of Audit Procedures" was held by the PKM Team. This Webinar will present expert speakers in this field to provide an in-depth understanding of audit procedures related to PSAK 72.This Webinar aims to help accounting professionals and auditors develop their knowledge and skills in facing fast and dynamic changes in the business environment. In this way, risks related to compliance can be reduced, and audit quality can be improved, thereby increasing stakeholder confidence in the reported financial information.Participation in the Webinar reflected high enthusiasm, with the number of participants increasing as the session progressed. The evaluation was conducted through an online survey, which showed that participants agreed that this Webinar provided significant benefits for their future. Furthermore, the survey results show that the objectives of this Webinar were well achieved, as reflected by the high level of agreement in the questionnaire. Thus, this Webinar provides an in-depth understanding of PSAK 72 and its audit procedures and meets participants' needs to increase professionalism and quality in accounting and audit practices amidst continuously developing business dynamics.